Differential clinical significance of pre-, interim-, and post-treatment plasma Epstein–Barr virus DNA load in NK/T-cell lymphoma treated with P-GEMOX protocol. Issue 8 (3rd July 2019) - Wang, Xiao-Xiao; Li, Peng-Fei; Bai, Bing; Gao, Yan; Rong, Qi-Xiang; Cai, Qing-Qing; Lin, Su-Xia; Zhang, Yu-Jing; Li, Zhi-Ming; Jiang, Wen-Qi; Huang, Hui-Qiang
Abstract: Circulating EBV-DNA is an accurate biomarker of tumor load in extranodal natural killer (NK)/T cell lymphoma (ENKTL); however, its role in patients treated with P-GEMOX has not been evaluated. In this study, we examined plasma EBV-DNA of 99 patients at different time points by real-time quantitative polymerase chain reaction. Multivariate analysis revealed that ECOG PS score, response rate, and post-treatment EBV-DNA level were independent predictors of progression-free survival (PFS) and overall survival (OS). Positive post-treatment plasma EBV-DNA was associated with poor OS in ENKTL patients. The 3-year OS for patients with positive pre-, interim-, post-treatment EBV-DNA was significantly lower than that for patients with negative EBV-DNA; the values were 70.2% vs. 93.9% ( p  = .022), 53.8% vs. 99.1% ( p  < .001), and 40.6% vs. 91.8% ( p  < .001), respectively. We conclude that monitoring dynamic changes in plasma EBV-DNA in ENKTL patients treated with P-GEMOX could predict important outcomes such as OS.